Book review: Bangura, Yusuf, editor. 2015: The Developmental Pathways to Poverty Reduction. (April 2017) - Ferris, Denise
Bangura, Yusuf, editor. 2015: The Developmental Pathways to Poverty Reduction . New York: Palgrave Macmillan. 338 pp. £75. ISBN: 9781137482532 (hardback). £71.25. ISBN: 9781137482549 (e-book).